CRISPR/Cas-directed programmable assembly of multi-enzyme complexes. Issue 36 (2nd April 2020) - Lim, Samuel; Kim, Jiwoo; Kim, Yujin; Xu, Dawei; Clark, Douglas S.
Abstract : We describe a versatile CRISPR/Cas-based strategy to construct precisely organized, scaffolded multi-enzyme systems with improved productivity. Abstract : We describe a versatile CRISPR/Cas-based strategy to construct multi-enzyme complexes scaffolded on a DNA template in programmable patterns. Catalytically inactive dCas9 nuclease was used in combination with SpyCatcher–SpyTag chemistry to assemble enzymes in a highly modular fashion. Five enzymes comprising the violacein biosynthesis pathway were precisely organized in nanometer proximity; a notable increase in violacein production demonstrated the benefits of scaffolding.